The Chaos of Post-Truth: The Devil and Lies - Lontoh, Frederich Oscar (Jurnal Teologi dan Pelayanan Kerusso, 2024)
The post-truth era has had a significant impact on the responses and behaviors of both individuals and groups. The characteristics of this era tend to blur objective facts and lead to relativism, where objective truth is no longer considered absolute. This situation triggers the spread of false news and the distortion of facts, causing individuals to become disseminators of lies or, at the very least, mislead others into logical fallacies far from objective truth. The purpose of this research is to analyze the impact of the post-truth era on individual behavior and thinking, as well as to uncover the factors contributing to the widespread dissemination of lies and manipulation of facts. This study also aims to understand the root causes of the chaos in the post-truth era from a theological perspective. This research employs a qualitative method with a library research approach. The researcher analyzes the variables used and presents them descriptively. The results of the study indicate that the chaos of the post-truth era stems from individuals being deceived, manipulated, and trapped in the allure of lies, diverting them from the objective truth that originates from God, and instead leading them towards subjective truth driven by personal desires and passions.